Peran Manajemen Keuangan Syariah dalam Pemenuhan Sarana Prasarana Pendidikan di Yayasan An-Nikmah Al-Islamiyah Phnom Penh Kamboja - Irzatul FIra; Rahmayati (MES Management Journal, 2024)
This research aims to analyze and understand the role of sharia financial management in providing educational infrastructure at the An-Nikmah Al-Islamiyah Foundation, Phnom Penh, Cambodia. This research uses a qualitative approach. Data collection techniques were carried out using interviews, observation and documentation. Data analysis techniques use data presentation, data reduction and conclusion/verification. Checking the validity of the data is carried out through; transferability, trust, dependability, and confirmability. The research results show that; Sharia financial management in the provision of educational infrastructure at the An-Nikmah Al-Islamiyah Phnom Penh Cambodia Foundation is carried out through planning and absorption of school budgets, school financial accounting, and school financial accountability. The implementation of Sharia Financial Management at the An-Nikmah Al-Islamiyah Foundation, Phnom Penh, Cambodia has been running optimally, however the implementation of sharia-based finance is not yet optimal, this is due to the low level of sharia financial support in that country.